IMPLEMENTASI MODUL LITERASI DASAR KESEHATAN MENTAL REMAJA MELALUI PENELITIAN TINDAKAN: Implementation of Adolescent's Mental Health Literacy Module: An Action Research - Kathleen Rachel; Anita Novianty (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Mental disorders are still a serious problem in Indonesia, particularly among adolescents. Until today, there’s an increase in psychological issues, i.e., anxiety, depression, trauma, and suicide. This community service project intended to identify the changes in the participants’ knowledge criteria before and after the implementation stage of the mental health literacy module. The module components that are implemented are stress identification, emotion perceptions, introduction to mental health issues, mental health diagram, mental health diagnosis, and the concept of mental health literacy. The participants in this community service project are students of a private middle school (n=12) and high school students (n=281) in DKI Jakarta. The design of the community service project is based on participatory action research. Data analysis uses the descriptive quantitative approach. It was found that the main cause of stress was academics for 58,36%, Stress labeling in the form of negative feelings for 23.39%, and 36.13% of the participants were able to correctly write down idioms of mental health states. The data indicate a common problem in adolescents’ management of academic responsibilities as it is a major stress source. With the low percentage of participants understanding the use of mental health states’ idioms, it is necessary for a thorough assessment of mental health literacy modules implementation techniques. Even though improvements must be made to the process of labeling abnormal situations, the participants showed the capability to acknowledge abnormal situations they experienced in their daily lives.